KESALAHAN BERBAHASA SUNDA PADA SISWA DWIBAHASAWAN DI SLTP TARUNA BAKTI BAN DUNG - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The aim o( this research is to investigate written Sundanese errors made by pupils o( SLTP Taruna Bakti Bandung. The results show that (our types o( errors were detected: phonological, morphological. syntactic, and lexical. The phonological errors are close related to such phonemes as Ia! and lul, Idl and Iyl, Idl and Irl, lei. and la!, 101and Iul. The morphological errors include types o(affixes, ego ber-, sa-, ter-. ke-an, di-i. The syntactic errors occur in the use o( the passive voice. The lexical errors include the use o( loan words or borrowings such as antusias, bakar. cerm